2017
DOI: 10.4306/pi.2017.14.1.16
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Crisis in Greece and Its Impact on the Seasonality of Suicides in the Athens Greater Area

Abstract: ObjectiveThe economic crisis and the implementation of austerity measures in Greece lead to significant socioeconomic changes. The effects of the crisis were mainly felt by the Greek population during the years 2011 and 2012. This study aimed to investigate the impact of Greece's economic crisis on the seasonality of suicides in the Athens Greater Area.MethodsData were collected for all recorded cases of suicides committed over a 5-year period (from 2008 to 2012) from the Athens Department of Forensic Medicine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Serotonin dysfunction has been linked to affective, anxiety and eating disorders, as well as migraine, all of which have been reported to have seasonal variations in symptoms (Brewerton, 1989; Brewerton, 1995; Brewerton and George, 1990; Brewerton and Jimerson, 1996; Hardin et al, 1991; Marazziti, 2017). In addition, behaviors connected to 5-HT dysfunction include certain forms of violence and impulsive behaviors, including suicide, homicide, sexual assault, and arson (Christodoulou, C. et al, 2012; Christodoulou, C. et al, 2012; Christodoulou et al, 2017; Christodoulou et al, 2009; Kattimani et al, 2016; Nader et al, 2011; Postolache et al, 2010; Vyssoki et al, 2012; White et al, 2015; Woo et al, 2012). Temperature has been reported to be significantly correlated to violent behavior, including assaults against women and suicides, especially by violent means (Anderson, 1989; Bushman et al, 2005; Cohn, 1990; Maes et al, 1993; Maes et al, 1994; McCleary et al, 1991; Michael and Zumpe, 1983, 1986; Rotton and Frey, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Serotonin dysfunction has been linked to affective, anxiety and eating disorders, as well as migraine, all of which have been reported to have seasonal variations in symptoms (Brewerton, 1989; Brewerton, 1995; Brewerton and George, 1990; Brewerton and Jimerson, 1996; Hardin et al, 1991; Marazziti, 2017). In addition, behaviors connected to 5-HT dysfunction include certain forms of violence and impulsive behaviors, including suicide, homicide, sexual assault, and arson (Christodoulou, C. et al, 2012; Christodoulou, C. et al, 2012; Christodoulou et al, 2017; Christodoulou et al, 2009; Kattimani et al, 2016; Nader et al, 2011; Postolache et al, 2010; Vyssoki et al, 2012; White et al, 2015; Woo et al, 2012). Temperature has been reported to be significantly correlated to violent behavior, including assaults against women and suicides, especially by violent means (Anderson, 1989; Bushman et al, 2005; Cohn, 1990; Maes et al, 1993; Maes et al, 1994; McCleary et al, 1991; Michael and Zumpe, 1983, 1986; Rotton and Frey, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Economou et al [39] as well as Christodoulou et al [40] found a significant increase of suicides and suicidal attempts between 2008 and 2010 further strengthening during 2011 and 2012. They stated that major depression was the strongest risk factor for this increase.…”
Section: Fluctuations Of Emotions During the Six Years Periodmentioning
confidence: 94%
“…39 Data from the Athens Department of Forensic Medicine, retrieved between 2008 and 2012, highlighted how seasonality played a significant role on suicide rates during the crisis with peaks in May and June. 51 Interestingly, a review of all suicide cases in the island of Crete (the largest island of Greece with the highest suicide mortality rates) between 1999 and 2013 reported no significant increase in suicides during the considered period, while suggesting a significant role of sociocultural factors, family ties, opportunity to emigrate, gun ownership, different expectations depending on one's age and gender. Finally, the bigger increase in suicides was registered in Eastern Crete, suggesting the impact of the lack of mental health services in that region.…”
Section: Suicidementioning
confidence: 99%